The Kv7.2/Kv7.3 Heterotetramer Assembles with a Random Subunit Arrangement - Stewart, Andrew P. (American Society for Biochemistry and Molecular Biology, 2012)
Voltage-gated K(+) channels composed of Kv7.2 and Kv7.3 are the predominant contributors to the M-current, which plays a key role in controlling neuronal activity. Various lines of evidence have indicated that Kv7.2 and Kv7.3 form a heteromeric channel. However, the subunit stoichiometry and arrangement within this putative heteromer are so far unknown. Here, we have addressed this question using atomic force microscopy imaging of complexes between isolated Kv7.2/Kv7.3 channels and antibodies to epitope tags on the two subunits, Myc on Kv7.2 and HA on Kv7.3. Initially, tsA 201 cells were transiently transfected with equal amounts of cDNA for the two subunits. The heteromer was isolated through binding of either tag to immunoaffinity beads and then decorated with antibodies to the other tag. In both cases, the distribution of angles between pairs of bound antibodies had two peaks, at around 90° and around 180°, and in both cases the 90° peak was about double the size of the 180° peak. These results indicate that the Kv7.2/Kv7.3 heteromer generated by cells expressing approximately equal amounts of the two subunits assembles as a tetramer with a predominantly 2:2 subunit stoichiometry and with a random subunit arrangement. When the DNA ratio for the two subunits was varied, copurification experiments indicated that the subunit stoichiometry was variable and not fixed at 2:2. Hence, there are no constraints on either the subunit stoichiometry or the subunit arrangement.